Novel Peripherally Restricted Cannabinoid 1 Receptor Selective Antagonist TXX-522 with Prominent Weight-Loss Efficacy in Diet Induced Obese Mice - Chen, Wei; Shui, Fengchun; Liu, Cheng; Zhou, Xinbo; Li, Wei; Zheng, Zhibing; Fu, Wei; Wang, Lili (Frontiers in Pharmacology, 2017)
The clinical development of the first generation of globally active cannabinoid 1 receptor (CB1R) antagonists was suspended because of their adverse neuropsychiatric effects. Selective blockade of peripheral CB1Rs has the potential to provide a viable strategy for the treatment of severe obesity while avoiding these central nervous system side effects. In the current study, a novel compound (TXX-522) was rationally designed based on the parent nucleus of a classical CB1R-selective antagonist/inverse agonist, rimonabant (SR141716A). Docking assays indicate that TXX-522 was bound with the CB1R in a mode similar to that of SR141716A. TXX-522 showed good binding, CB1R-selectivity (over the CB2R), and functional antagonist activities in a range of in vitro molecular and cellular assays. In vivo analysis of the steady state distribution of TXX-522 in the rat brain and blood tissues and the assay of its functional effects on CB1R activity collectively showed that TXX-522 showed minimal brain penetration. Moreover, the in vivo pharmacodynamic study further revealed that TXX-522 had good oral bioavailability and a potent anti-obesity effect, and ameliorated insulin resistance in high-fat diet-induced obese mice. No impact on food intake was observed in this model, confirming the limited brain penetration of this compound. Thus, the current study indicates that TXX-522 is a novel and potent peripherally acting selective CB1R antagonist with the potential to control obesity and related metabolic disorders.